La mediación y petición en el libro de Joel y su relación con Jonás - Sanz Giménez-Rico, Enrique (Scripta theologica, 2018)
The collaboration, familiarity, and harmony between God and the prophet, as well as the prophet's mediation, which appear in the first part of the Book of Joel, prompt a process of intercession in the assembly of the people. This process concludes in Joel 2:17 with a sincere and profound petition centered on God's mercy. The themes of God's mercy and prophetic mediation, which are particularly relevant to the Book of the Twelve, run through this article, which focuses on the reading of the first part of Joel and the Book of Jonah. The development of these themes leads to the article's main conclusions about the essence, content, and form of the prayer of petition.